100 Years of Solitude: A Century of Newspapers in the David M. Rubenstein Rare Book and Manuscript Library. Issue 3 (2nd October 2017) - Janecki, Jessica
ABSTRACT: In 1898, the Trinity College Historical Society began collecting the first newspapers that would become the foundation of the Rubenstein Rare Book and Manuscript Library's historical print newspaper collection. In recent decades, these newspapers lay underdescribed and largely inaccessible in a Rubenstein alcove. Impending renovation forced action, and in 2012 a three-year, multidepartment project to describe and house the collection was launched. In January 2016, the project successfully concluded, providing for the first time intellectual and physical control of the collection. Four years' worth of circulation data show steady and consistent usage on par with the greater Rubenstein collection.